CITRONELLOL: A POTENTIAL ANTIOXIDANT AND ALDOSE REDUCTASE INHIBITOR FROM CYMBOPOGON CITRATUS - Jagdale, Ashwini Dinkar; Kamble, Snehalata Prakash; Nalawade, Megha Laxman; Arvindekar, Akalpita Umesh (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
Objective: The present study deals with identification of bioactive component from the distillate of Cymbopogon citratus plant and to evaluate its aldose reductase inhibitory and antioxidant activity. Methods: The aldose reductase enzyme was semi purified by ammonium sulphate precipitation from chicken eye lens. Differential solvent extraction of Cymbopogon citratus was carried out and by using HPLC, HPTLC and Gas chromatography active component responsible for aldose reductase inhibition was identified. The Oral Glucose Tolerance Test was carried by induction of diabetes to the male Wistar rats with streptozotocin. The sorbitol content was measured by sorbitol dehydrogenase enzyme. The antioxidant activity was studied using DPPH and FRAP methods. Results: Differential solvent extraction of the distillate revealed presence of aldose reductase inhibitory activity in the petroleum ether extract of the plant. Citronellol was identified as bioactive component by HPLC, HPTLC and gas chromatography. Citronellol demonstrated 90.4% inhibition of aldose reductase with an IC50 value of 19.6 Â±0.8 Âµg/ ml as against 92.3 % inhibition by the standard drug epalrestat with an IC50 value 9.8 Â±0.43 Âµg/ ml. It demonstrated better lowering of sorbitol (44%) than epalrestat (28%) in the eye lens studies as compared to the diabetic control. Kinetic studies using Lineweaver Burk Plot revealed citronellol to be a mixed type of inhibitor. Docking studies revealed the binding of citronellol at a site similar to epalrestat. Conclusion: Citronellol from C. citratus is found to possess potent aldose reductase inhibitory activity with mixed type of enzyme inhibition and a very good antioxidant potential. Â